Histological analysis of the effects of thymoquinone on testicular damage in pentylenetetrazole-induced temporal lobe epilepsy model - ŞİRVANCI, SERAP (WILEY, 2021)
In this study, it was aimed to investigate possible ameliorating effects of thymoquinone on testicular damage in an epilepsy model. Adult male Wistar rats were divided into 4 groups. The animals in sham-operated groups were given saline or thymoquinone (s.c.); and the animals in pentylenetetrazole (PTZ) group were applied PTZ. The animals in PTZ+thymoquinone group were given thymoquinone (i.p) for 6 days after applying PTZ. Hematoxylin-eosin, periodic acid-Schiff and TUNEL staining and PCNA, StAR, inhibin beta-B immunohistochemistry and ZO-1 immunofluorescence methods were applied. Staining intensity and cell numbers were determined. Degeneration of seminiferous tubules was observed in PTZ group. Most of the tubules showed normal morphology in the PTZ+thymoquinone group. Apoptotic cell index was found to be increased and proliferative index decreased in PTZ group. Thymoquinone administration decreased apoptotic index and increased proliferation index. In PTZ group, ZO-1, StAR and inhibin beta-B immunohistochemical staining intensity was observed to be decreased and after thymoquinone application, ZO-1 was increased. StAR and inhibin beta-B-positive cell numbers were decreased in PTZ group and increased in the PTZ +thymoquinone group. In this study, it was observed that PTZ-induced epileptic seizures caused testicular damage in the rat and thymoquinone ameliorated these effects.
Keywords: kindling; pentylenetetrazole; temporal lobe epilepsy; testis; thymoquinone; GERM-CELL APOPTOSIS; TASK-FORCE; TESTIS; DYSFUNCTION; SEIZURES; CADMIUM; PROTEIN; ANTIOXIDANTS; EXPRESSION; FERTILITY